Professional Ethics of Judges: A Normative Study of Ethical Violations and Their Implications for Public Perception - Realizhar Adillah Kharisma Ramadhan; Irfan Syafar (Cita konsultindo, 2025)
This study aims to normatively examine the ethics of the judicial profession in Indonesia as regulated in the Code of Ethics and Guidelines for Judges' Conduct (KEPPH), and to analyze the implications of ethical violations on public perception of judicial institutions. Although KEPPH has established basic principles such as integrity, independence, and impartiality, practice in the field still shows many ethical violations by judges, including bribery, conflicts of interest, and inappropriate behavior. Through a legislative, conceptual, and case study approach, this study finds that ethical violations have a serious impact on the legitimacy of judicial institutions and reduce public trust. Negative public perception of the integrity of judges strengthens procedural injustice and weakens the principle of the rule of law. This study recommends strengthening supervision, institutional culture reform, and continuous ethical education as strategic steps to improve the integrity of the judicial profession and restore public trust.